Quasi‐Harmonic Lattice Dynamics of a Prototypical Metal–Organic Framework. Issue 11 (19th July 2019) - Ryder, Matthew R.; Maul, Jefferson; Civalleri, Bartolomeo; Erba, Alessandro
Abstract: Quasi‐harmonic lattice‐dynamical calculations are performed to investigate the combined effect of temperature and pressure on the structural and mechanical properties of a prototypical metal–organic framework material: MOF‐5. The softening upon compression of an A 2 g phonon mode at the Γ point in the high‐symmetry F m 3 ¯ m structure is identified, which leads to a symmetry reduction and a group–subgroup phase transition to a low‐symmetry F m 3 ¯ phase for compressions larger than 0.8%. The effect of the symmetry reduction on the equation‐of‐state of MOF‐5 is investigated, which provides a static bulk modulus K reducing from 17 to 14 GPa and a corresponding change of K ′ (pressure derivative of K ) from positive to negative. The effect of pressure on the negative thermal expansion of the framework and on its mechanical response is analyzed. The evolution of the mechanical anisotropy of MOF‐5 as a function of pressure is also determined, which allows identifying the occurrence of a shear‐induced mechanical instability at 0.45 GPa. Abstract : Structural and mechanical features of the prototypical metal–organic framework, MOF‐5, are studied as a function of temperature and pressure from quasi‐harmonic lattice‐dynamical calculations. Quantum‐mechanical calculations are performed with a hybrid functional of the density functional theory. MOF‐5 is found to undergo a symmetry‐breaking phase transition upon structural compression, which significantly affects its mechanical properties.